2013
DOI: 10.3402/tellusa.v65i0.18171
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal fractions verification for high-resolution ensemble forecasts

Abstract: A B S T R A C T Experiments with two ensemble systems of resolutions 10 km (MF10km) and 2 km (MF2km) were designed to examine the value of cloud-resolving ensemble forecast in predicting precipitation on small spatio-temporal scales. Since the verification was performed on short-term precipitation at high resolution, uncertainties from small-scale processes caused the traditional verification methods to be inconsistent with the subjective evaluation. An extended verification method based on the Fractions Skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 30 publications
4
103
0
Order By: Relevance
“…These results are comparable to the main outcomes of Le Duc et al (2013) and Schwartz et al (2009). Le Duc et al (2013) also found that the coarser 10 km ensemble showed slightly better results for light rains than the finer 2 km one.…”
Section: Fractions Skill Scoresupporting
confidence: 77%
See 3 more Smart Citations
“…These results are comparable to the main outcomes of Le Duc et al (2013) and Schwartz et al (2009). Le Duc et al (2013) also found that the coarser 10 km ensemble showed slightly better results for light rains than the finer 2 km one.…”
Section: Fractions Skill Scoresupporting
confidence: 77%
“…Le Duc et al (2013) also found that the coarser 10 km ensemble showed slightly better results for light rains than the finer 2 km one. Both models had lower skill in predicting heavy rain; however, for the higher precipitation thresholds, the 2 km ensemble performed better than the 10 km one.…”
Section: Fractions Skill Scorementioning
confidence: 68%
See 2 more Smart Citations
“…Since the ICP special collection, a large number of papers have been published making use of the newer spatial techniques. For example, neighborhood methods [particularly the fractions skill score (FSS)] have been employed by Weusthoff et al (2010), Schaffer et al (2011), Sobash et al (2011, Duc et al (2013), Mittermaier et al (2013), and Skok and Roberts (2016). Scale separation methods have been used by De Sales andLiu et al (2011), and field deformation approaches by Nan et al (2010).…”
Section: The Setup Of the Mesovict Projectmentioning
confidence: 99%